Inomhusklimat i vårdlokaler. Mätstudie och underlag för kravformulering. - Ericsson, Jonas; Rydberg, Fredrik (My University, 2006)
In this study the conditions for indoor climate in hospital wards are examined to see if today s standards for indoor climate provide for medical service s special requirements. The purpose of this study is to determine today s rules and regulations applicability in hospital wards. This is done by measurements in different medical wards. The ambition is that the report could perform the function of basic data for recommendations of indoor climate in hospital wards. Several civil service departments, public authorities and trade associations issues rules and regulations upon indoor environment in different categories of buildings of witch only a few are specific for medical wards. The standards used for hospital wards today are foremost adapted to conditions in commercial buildings. In this report the rules and regulations, valid for indoor climate, used in hospital wards today is compiled. Furthermore application of the rules and regulations in the projecting process is accounted for, based upon information of designers and technical personnel as well as technical specifications. Great importance has been attached to present the fundamental theory of today s standards in a general way. The primary aim of the presentation of the theory is to elucidate how today s standards meets the requirements on the indoor climate of medical work, the presentation also intend to broaden the applicability of the theory. To illustrate the condition for the thermal climate and the air quality medical rooms have been categorized assorted after their characteristic conditions and loads. A relatively broad study of measurement has been performed in five hospital wards it involves measurements of temperature, relative humidity and concentration of particles and it also examines the perception of the indoor climate by questionnaires. The problem with perception of dry air in hospital wards is stressed. The categorization of medical rooms forms a basis of selection of representative rooms in each hospital ward. The study s first interest is those spaces where specified demands on the indoor climate for medical work are missing. The results of the measurements are presented to make the indoor climate in the five hospital wards known. To show the consequences of management and construction of the heating and HVAC installations the results are analysed together with information gathered from technical documentation describing the five hospital wards. By relate given levels of today s standards with measured levels and the results of the questionnaire are the present regulations ability to provide for medical services special requirements of indoor climate evaluated. Results of the study show that independently of measured relative humidity the occupants have a desire for a higher level of humidity. Due to the lack of relationship the perception of dry air could be presumed to be depending on for example some contamination in the air. Results of performed measurements show however no exceptional high concentrations of particles. Concerning thermal comfort the difficulties in regulate the climate factors independently is shown by the results of measurement.
Keywords: Byggnadsteknik; Building engineering